Needs Analysis and Development Design of Liveworksheet Based Numbered Head Together (NHT) Cooperative Model to Improve Students' Mathematical Problem Solving Ability - Junaidi, Junaidi; Lu'luilmaknun, Ulfa (JDIME: Journal of Development and Innovation in Mathematics Education, 2023)
This research is motivated by the importance of developing Student Worksheets (LKPD) tailored to the demands of the technological era, as students rarely encounter software-based LKPD that facilitates understanding of the material and is easily portable. Therefore, the researcher developed electronic LKPD based on Liveworksheet with the cooperative model Numbered Head Together (NHT). This development aims to enhance students' mathematical problem-solving abilities in the material of curved surface space. The development model employed by the researcher is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), known for its systematic, structured, directed, and planned development process. The study utilized a research instrument in the form of a questionnaire distributed to ninth-grade students in junior high school (SMP). The questionnaire aimed to identify the characteristics of participants and the needs of students regarding the developed LKPD. Based on the analysis of these needs, the researcher successfully developed electronic-based LKPD using the Liveworksheet platform. This LKPD product exhibits advantages in terms of efficiency and effectiveness, incorporating audio-visual elements and student discussions to build understanding and problem-solving skills. It is anticipated that this development will provide an interactive, engaging learning experience and assist students in developing mathematical problem-solving skills.